The feasibility of using bentonite, illite, and zeolite as capping materials to stabilize nutrients and interrupt their release from contaminated lake sediments - Gu, Bon Wun; Hong, Seung Hee; Lee, Chang Gu; Park, Seong Jik (Chemosphere, 2019)
The aim of this study was to assess the feasibility of using bentonite, illite, and zeolite as capping materials to interrupt the release of and sequestrate carbon, nitrogen, and phosphorus from contaminated sediments. Their efficiency was assessed in batch isotherm, column incubation experiments, and nitrogen and phosphorus extraction from the capping materials and sediments. All capping materials contributed to the reduction of dissolved oxygen depletion and chemical oxygen demand in overlying water. Zeolite showed a high adsorption capacity for NH4-N; the zeolite cap produced the lowest NH4-N flux constituting the highest percentage of total nitrogen in the overlying water. Significant changes in water conditions, such as an increased pH (>8) and lowered oxidation reduction potential (<−80 mV) were observed when a bentonite cap was used. Illite showed high capping efficiency (>130%) for both PO4-P and total phosphorus, and phosphorus was adsorbed mainly as the high residual-P fraction (≈90%) in its strongest adsorbed form. The results of this study indicate that illite has potential for use as an agent to deactivate phosphorus in lake eutrophication control techniques.
Keywords: Capping; Contaminated sediment; Eutrophic lakes; High adsorption capacity; Illite; Lake eutrophications; Nitrogen and phosphorus; Oxidation reduction potential; Bentonite; Geologic Sediments; Lakes; Minerals; Water Pollutants, Chemical; Zeolites; Bentonite; Capping; Eutrophic lake; Illite; Sediment; Zeolite